Pemanfaatan Google Classroom sebagai Media Pembelajaran di Masa Pandemi di MI Unwanul Falah - Izzati, Izzati (Lembaga Yasin AlSys, 2021)
The Covid-19 pandemic that has hit the world for more than a year has had an impact on changes in teaching and learning activities. This country is no exception, since March 2020 online learning activities have become an option for the ministry of education and culture to prevent the spread of the Covid-19 virus from expanding. The practice of online education (one year online learning) is carried out by various levels of education. There are no more learning activities in classrooms as is usually done by teacher educators and lecturers. Nowadays, internet literacy has become a very important role to be developed in our basic life. Therefore, the education sector needs to use information technology in the learning process both in schools and in higher education. Google Classroom is an access that makes it easier for educators in the learning process. This is the right step, as a result, many educators are not ready to face this drastic change in teaching methods. Meanwhile, there is practically no other way to minimize the spread of Covid-19 other than by limiting human encounters in large numbers through social distancing measures. The government has also limited gatherings to a maximum of 30-40 people. Even then, with very strict health protocols, namely the use of masks, maintaining a minimum distance of 1.5 meters and washing hands with soap. This is based on the opinion of health experts around the world after they conducted research on how to break the chain of Covid-19.